Genetic variability and population structure of the begomovirus Euphorbia yellow mosaic virus and its associated alphasatellite - Mar, Talita Bernardon (2017)
The emergence of begomoviruses (whitefly-transmitted viruses classified in the genus Begomovirus, family Geminiviridae) in Brazil probably occurred by horizontal transfer of viruses infecting non-cultivated plants after the introduction of Bemisia tabaci MEAMl. Recently, Euphorbia yellow mosaic alphasatellite (EuYMA) was found in association with Euphorbia yellow mosaic virus (EuYMV) infecting Euphorbia heterophylla, an important invasive species in soybean and other crops in Brazil. We assessed the genetic variability and population structure of begomoviruses infecting E. heterophylla, and the geographical range of alphasatellites in samples collected throughout nine Brazilian states from 2009 to 2014. Only EuYMV was detected (with one exception), and a total of 158 and 57 haplotypes were compared in DNA-A and DNA-B datasets, respectively. EuYMA was detected in only six samples collected in the states of Rio Grande do Sul and Paraná. Compared with other begomoviruses, EuYMV has a low degree of genetic variation, and few intraspecific recombination events. The application of principal component analysis allowed the differentiation of six viral subpopulations according to sampling locations, in agreement with phylogenetic analysis. The polymorphisms of 23 sites that mostly contributed to the geographical structure were shown to hold supporting information to discriminate between the viral subpopulations. Biological and molecular aspects of the association between the alphasatellite EuYMA and EuYMV were studied following the construction of infectious clones of both agents. Phenotypic differences of EuYMV infection in the presence of EuYMA were observed in Arabidopsis thaliana, Nicotiana benthamiana and E. heterophylla. Transmission assays indicated that EuYMA negatively affects the transmission of EuYMV by Bemisia tabaci MEAMl. Together, the results indicate that EuYMV displays a lower degree of genetic variation compared to other begomoviruses infecting cultivated and non-cultivated plants in Brazil but, similar to other begomoviruses, segregates according to sampling location, and that EuYMA is capable of modulating symptoms, Viral accumulation and whitefly transmission of EuYMV, potentially interfering with Virus dissemination in the field.